Effect of binder on oxidation properties of tungsten carbides: A review by a Conceptual Classification Approach - Fathipour, Zahra (2024)
This study presents a conceptual classification scheme to review the literature on improving the oxidation resistance of tungsten carbide by modifying the binder. The first parts of the article are dedicated to the specification of the databases, the search method, and the description of the criteria chosen to classify the articles. Then, the data collected are presented in statistical graphs according to the proposed classification scheme. The data analyzed show that most of the significant improvements in oxidation resistance are achieved with advanced production processes, especially HIP and SPS, which eliminate porosity to a very high degree. In addition, statistical studies showed that the use of new replacement binders, Ni3Al, Fe–based alloys, FeAl, and Al2O3, improved the oxidation properties in 75–100% of cases. Meanwhile, the use of high–entropy alloys (HEAs) as cermet binders may be the subject of future research for oxidation, given the recently published results of good mechanical properties.